2021
DOI: 10.37121/jase.v5i1.157
|View full text |Cite
|
Sign up to set email alerts
|

Estimated billing system is the bane of grid electric power supply and development in Nigeria: An empirical analysis

Abstract: The estimated billing system for electricity was introduced in Nigeria by the Nigerian Electricity Regulatory Commission (NERC) in 2012 for billing customers without meters or with faulty or inaccessible meters. But instead of following the guidelines and formula provided by NERC for the estimation, the electricity Distribution Companies (DisCos) resorted to billing these customers arbitrarily and frustrated efforts by NERC to ensure the proper metering of electricity consumers. This research evaluates the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The numerical value of the daily mean value of extraterrestrial radiation can be computed using the Equation [4] given by Sanusi et al (30)…”
Section: Solar Irradiance and Ambient Temperature Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical value of the daily mean value of extraterrestrial radiation can be computed using the Equation [4] given by Sanusi et al (30)…”
Section: Solar Irradiance and Ambient Temperature Resourcesmentioning
confidence: 99%
“…Olabode) indeed has become a monster that seems insurmountable (2). It is not gainsaying that the erratic supply of energy has contributed in no small measure to the incidence of lingering poverty that has crippled the growth and development of many industries (local or foreign) and commercial centers in many developing countries around the globe (3,4). This irregularity of energy supply from the national grid is so bad that owners of companies, commercial businesses, and residential buildings among others cannot no longer predict when supply from the national grid will be made available for their utilization (5,6).…”
mentioning
confidence: 99%
“…In addition, the result may be explained by the record of huge estimated bills (that do not depend on the actual energy consumed) paid by unmitigated or non-prepaid residents who do not have access to a smart prepaid electricity meter. An empirical study found that non-prepaid or unmetered customers are often highly overbilled (Ohajianya, 2021), and about 80% of consumer complaints received by the NERC are about estimated and excessive bills (Arimoro et al, 2019). Similarly, the continuous skyrocketing of fuel prices over the years has made it practically and economically difficult for households to sustain the use of generators as an alternative source of power, except for commercial and energydependent outfits, and a few well-to-do families.…”
Section: Ef (Gha) Percentmentioning
confidence: 99%
“…Inadequate and erratic power supply has been blamed amongst other factors responsible for high mortality at LMIC health facilities [9]. The health facilities in Nigeria are notoriously crippled by incessant power blackouts, including at high vulnerability hospital segments such as the SCBU [10]. Hence, some useful methods of alternative or supplementary power provision have been suggested, including the use of solar panels and inverter technology [11].…”
Section: Building With Intent To Enhance Low-cost Facility Lighting A...mentioning
confidence: 99%